Polycystic kidney disease in a Persian cat - Phoon, Melissa Hoi Ee; Khor, Kuan Hua; Lau, Seng Fong; Saw, Ming Hooi (Veterinary Association Malaysia, 2015)
A 6-year-old intact Persian cat was presented for the primary complaint of inappetence and weight loss. Irregular surface of kidneys was palpated during physical examination. Abdominal radiograph findings were indicative of renomegaly. Ultrasonography revealed multiple anaechoic structures within the renal parenchyma. The cortex, medulla and renal pelvis were unable to be differentiated. Both radiographic and ultrasonographic findings were suggestive of polycystic kidney disease. Blood test revealed normochromic, normocytic anaemia with azotaemia whereas urinalys is findings were hypostenuria and proteinuria, consistent of chronic kidney disease due to polycystic kidney. Ultrasound is a useful antemortem diagnostic tool to diagnose polycystic kidney disease in cats.